Digital Platforms for Mathematics Teachers: A Learning Ecosystem for the Future Digital World - Kulmart, Khemisara (Journal of Education Studies, Chulalongkorn University, 2024)
The digital platform aims to create a learning ecosystem that develops skills for the digital world and the future, specifically tailored for mathematics ‘teachers, aims to 1) create and develop a digital platform to build a digital and future-ready educational environment for mathematics teachers 2) study the acceptance and confidence in the digital platform for developing digital and future-ready skills among mathematics teachers and 3) disseminate, transfer, and apply technology to create opportunities, equality, and educational coverage across all areas. The target group consists of mathematics teachers in the educational innovation zone of Narathiwat Province, totalling 94 people. Research participants were selected on a voluntary basis. The research tools used include the digital environmental education platform, named P'TAM, a digital learning outcome assessment, and acceptance and confidence surveys. Data analysis was conducted using basic statistics, including percentages, average numerical values, and standard deviations. The research results found that: 1) Digital platform quality assessment: Experts evaluated the digital platform, achieving a high level of quality. The results of online learning by mathematics professionals reached 91.01%, exceeding the 70% benchmark. 2) Acceptance and confidence in the Learning Platform: The study found high levels of acceptance and confidence in the learning platform, with a mean score of 4.30 and a standard deviation of 0.7. And implementing digital technology integration in E-learning to foster a digital learning ecosystem and global digital skills. This initiative aims to create opportunities for equal access and inclusive education, covering all areas by integrating digital technology into teaching and learning through a digital platform.